Growth of Cinta Senese piglets as affected by location of the suckled teat - Martina Bianchi; Anna Acciaioli; Clara Sargentini; Oreste Franci (Italian Journal of Animal Science, 2010)
The experimental animals were 18 Cinta Senese sows (7 primiparous and 11 multiparous) and relative purebred off-  spring. Individual weight of piglets was recorded at birth (or shortly afterwards) to the nearest 50 g and subsequently  every 3-5 days up to weaning. At each recording, piglets were ranked in decreasing order according to weight within their  respective litters. The behavior of a subsample of 8 sows and litters was observed during suckling, by recording the  teat–piglet coupling. The sows had 12 functional teats, equally distributed in the two symmetric rows, that were num-  bered as pairs in the antero-posterior direction.  Starting from the third week, piglets of multiparous sows showed a faster growth rate than those of the primiparous ones.  Repeatability of the piglets’ weight during the suckling period was high (r = 0.56) and repeatability of rank was even  higher, but decreased up to weaning. Anterior teats were the most occupied and showed the highest suckling fidelity  (consistency of suckling position). Various statistical analyses about the dependence of piglet weight (or weight rank with-  in litter) on teat order indicated the highest milk productivity of the first teats and the lowest of the 5th & 6th teat pairs.